Determinants of Food Insecurity Status among Cocoa Farmers in Ondo State, Nigeria. - Dada, O.A.; Oluyole, K.A; Oladokun, Y.O.M; Awodumila, D. (Indonesian Coffee and Cocoa Research Institute, 2024)
Food insecurity is a lack of consistent access to enough food for every person in a household to live an active and healthy life. This can be a temporary situation for a family or can last a long time. Food insecurity is one way to measure people’s food affordability. The aim of the study was to determine factors that affect food insecurity status among cocoa farming households in Ondo state, Nigeria. Multi-stage random sampling technique was used to select the respondentfarmers for the study. The first stage was the purposive selection of three Local Government Areas (LGAs) from the State. Second stage was the random selectionof 15 cocoa producing communities from the three selected LGAs (the selection was proportional to size), while the third stage was the random selection of 400cocoa farming households from the selected communities. Data were collected with the use of structured questionnaires and analyzed using descriptive statistics and Probit regression analysis. Results revealed that the majority (73.8%) of the respondents were males, out of which 84.2% were literates with at least primary school education, while (93.7%) of the respondents had enough farming experience of more than 10 years. The major significant variable determinants of food insecurity in the study area were total household income, age, household size, level of education, membership of cooperative, access to credit and farm size. It is therefore recommended that farmers should be granted more access to credit facilities at low interest rates as this further guarantees their food security.